2011
DOI: 10.1080/09712119.2011.565222
|View full text |Cite
|
Sign up to set email alerts
|

Performance and antibody response of broiler chickens fed diets containing probiotic and prebiotic

Abstract: To determine the influence of yeast culture-based prebiotics and lactobacillus-based probiotic culture on the performance and immune response, 360 male Ross broiler chickens were divided in three groups with four replicates each. A corn-soybean meal-based diet was either unsupplemented (Control) or supplemented with either 3 g/kg prebiotics (gr 2) or 0.9, 0.45 g/kg probiotic and fed to chicks for 42 days. Body weight and feed/gain ratio improved by supplementation of prebiotic (p B0.05) only. Antibody response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…One of the proposed mechanisms responsible for benefits of probiotic is an immunomodulatory effect (Salianeh et al 2011). Some investigators demonstrated the potential effect of probiotic on immunomodulation (Nayebpor et al 2007;Apata 2008).…”
Section: Introductionmentioning
confidence: 98%
“…One of the proposed mechanisms responsible for benefits of probiotic is an immunomodulatory effect (Salianeh et al 2011). Some investigators demonstrated the potential effect of probiotic on immunomodulation (Nayebpor et al 2007;Apata 2008).…”
Section: Introductionmentioning
confidence: 98%
“…FPCM slightly increased the growth rate of chicks. Another study also showed the positive effects of a prebiotic (Saccharomyces cerevisiae yeast culture) on BWG and FE in 1-to 42-day-old broilers (Salianeh et al 2011). …”
Section: Growth Performancementioning
confidence: 99%
“…Therefore, a lot of researchers have partially replaced antibiotics with probiotics as therapeutic and growth promoting agents. It was reported that probiotics have a good impact on the poultry performance by stimulating appetite (Nahashon et al 1994), improving intestinal microbial balance (Fuller 1989), synthesising vitamins (Coates and Fuller 1977), stimulating the digestive enzyme (Saarela et al 2000), utilising undigestible carbohydrates (Salianeha et al 2011), stimulating lactic acid, decreasing pH and releasing bacteriocins (Rolfe 2000). Pedroso et al (1999) have reported that the use of probiotics improved feed conversion and eggshell thickness.…”
Section: Introductionmentioning
confidence: 99%